Modelling leaf gas exchange in holm-oak trees in southern Spain (Agricultural and Forest …, 1999)
This paper presents a mechanistically based C3 leaf CO2 assimilation model linked with an empirical stomatal model to simulate Quercus ilex leaf net photosynthesis and transpiration in oak-savannah ecosystems of southern Spain. The model estimates (time integration) daily and seasonal changes in carbon ®xation, transpiration, and water use ef®ciency of a single leaf in free air. Simulations were carried out on two trees for a dry year. Results shown in our study demonstrate that the modelling approach, compared to ®eld measurements, provides a realistic description of diurnal and seasonal patterns of leaf gas-exchange response to different environmental conditions, and as affected by water availability